Budgetary balances adjustments from governmental accounting to national accounts in EU countries: can deficits be prone to management? - Jorge, S. (2018)
European Union (EU) countries are required to achieve deficit targets and are thus incentivized to use tools to keep within budgetary limits. This paper argues that accounting discretion might be used to manage some adjustments made during the translation of data from Governmental Accounting (GA) into National Accounts (NA), to window‐dress the final deficit/surplus reported to EUROSTAT. The empirical research shows there are certain circumstances that might facilitate the use of GA–NA “adjustment discretion.” EU authorities must pay special attention to these conditions to ensure the reliability of reported deficits. The main findings of this paper could also assist in future efforts to improve the integrity of the adjustment process.